On Boolean semiring partitioning - Justus, Claudia Ledbury (Stellenbosch : Stellenbosch University, 2025)
Justus, C. L. 2025. On Boolean semiring partitioning. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4c2c87b4-e49a-4b02-99cb-171b299e3e27